Mortandad de Gorgonia flabellum Linneaus (Octocorallia: Gorogoniidae) en la Costa del Caribe de Costa Rica - Guzmán Espinal, Héctor M. (1984)
During 1982, the population of the coral Gorgonia flabellum started to die on the Caribbean coast of Costa Rica. Seven possible causes were analyzed: temperature-salinity variation, sedimentation, predation, wave action, bioerosion, pollution and diseases. The pathology of "Black band" disease coincides with our observations. Death of other octocorallia was not observed. This is the first time that mass mortality of G. flabellum is reported.